ANALISIS PERBANDINGAN RETURN ON ASSETS (ROA) DAN DEBT TO EQUITY RATIO (DER) TERHADAP NILAI PERUSAHAAN PADA PT NUSA RAYA CIPTA TBK DAN PT JAYA KONSTRUKSI MANGGALA PRATAMA TBK - Yumiarni, Nani; Puji Muniarty (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to analyze the comparison of Return On Assets (ROA) and Debt to Equity Ratio (DER) on firm value at PT Nusa Raya Cipta Tbk and PT Jaya Konstruksi Manggala Pratama Tbk. This research uses a quantitative approach with a comparative method. The data used are secondary data obtained from the companies’ financial statements for the period 2015–2024. The data analysis techniques include normality testing using Shapiro-Wilk and comparative analysis using the Mann-Whitney test. The results show that Debt to Equity Ratio (DER) has a significant difference between the two companies, while Return On Assets (ROA) and firm value do not show significant differences.These findings indicate that the main difference lies in the capital structure, while profitability and firm value are relatively similar.